Issues and challenges of haulage industry after liberalization - Melan, Mustakim; Sabar, Rohafiz (Universiti Utara Malaysia, 2014)
This paper identifies the issues and challenges of haulage industry towards competitive businesses in the market of transportation.The objective of study is to examine the haulage industry from beginning of its establishment, competitiveness and saturation of its business.The first haulage company was established as haulage services in 1971 with only one driver and three vehicles. Due to robust demand of the containerized business in 1980s, the industry expended tremendously. Between the year 1990 to 2000, the haulage industry recorded a total of five (5) large companies controlling the market of haulage transportation.The overall total of prime movers and trailers at this period were approximately 1000 and 7,000 respectively.In 2004 the government introduced the open market concept called liberalization.In 2010, statistic indicated that the total overall operators had increased to 200 companies with approximately 4000 prime movers and 28,000 trailers.The overall increase of fleets in 10 years was approximately 400 % or about 40% per year. On the other hand, the haulage markets recorded only from 8 to 12 % annually.The oversupply of fleets had caused other problems especially in the operational activities and in demand for haulage services.At the same time, the haulage industry also incurred with higher overhead costs to maintain the overall fleets and manpower requirements. Several initiatives had been implemented for improvement in order to maintain sustainability in the haulage market. However the condition of haulage industry still unchanged and saturated.